2018
DOI: 10.1093/ecco-jcc/jjy086
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA Integrity is Unaffected by Thiopurine Treatment in Men With Inflammatory Bowel Disease

Abstract: Thiopurines do not increase sperm DNA fragmentation but may impair sperm motility in this IBD cohort. Our findings support existing epidemiological data that thiopurine therapy is safe during preconception and should not be abandoned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Four studies that included a total of 75 cases and 40 controls exposed to azathioprine were included ( Baumgarten et al , 1977 ; Farthing and Dawson, 1983 ; Dejaco et al , 2001 ; Grosen et al , 2019c ). Sperm quality, sperm DNA fragmentation index (DFI) and the male endocrine reproductive axis appear not to be negatively affected by azathioprine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies that included a total of 75 cases and 40 controls exposed to azathioprine were included ( Baumgarten et al , 1977 ; Farthing and Dawson, 1983 ; Dejaco et al , 2001 ; Grosen et al , 2019c ). Sperm quality, sperm DNA fragmentation index (DFI) and the male endocrine reproductive axis appear not to be negatively affected by azathioprine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of AZA in IBD patients did not generally report negative effects on semen quality, 40,59,60 although Farthing et al observed an increased percentage of oligo‐ and asthenozoospermia in 5 patients treated with AZA 11 . This study, however, did not report results for each patient, and therefore, it is not possible to evaluate them within the current WHO guidelines 4 .…”
Section: Resultsmentioning
confidence: 73%
“…Grosen et al further reported lower total and progressive motility in patients treated with AZA/6‐MP compared with healthy controls, although this was still in the reference values provided by WHO 4,59 . In addition, AZA/6‐MP did not appear to negatively affect sperm DNA integrity evaluated by using sperm chromatin structure assay (SCSA) and COMET assays 59 . IBD patients treated with MTX were reported in one study, in which patients were concurrently treated with IFN inhibitors or 5‐ASA 61 .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Dejaco et al[58] showed that the sperm quality of 18 IBD patients was not altered after 3 months of using azathioprine. In a cohort of 40 IBD men[59], thiopurines did not decrease sperm quality but was sometimes associated with the impairment of sperm motility. Methotrexate (MTX) can be responsible for oligospermia and is reversible after stopping usage; this drug is contraindicated for both women and men because it is embryotoxic[60].…”
Section: Fertilitymentioning
confidence: 99%